Vagus nerve stimulation in dementia: A scoping review of clinical and pre-clinical studies - Ronald Kamoga; Godfrey Zari Rukundo; Samuel Kalungi; Wilson Adriko; Gladys Nakidde; Celestino Obua; Johnes Obongoloch; Amadi Ogonda Ihunwo (AIMS Neuroscience)
Background Dementia is a prevalent, progressive, neurodegenerative condition with multifactorial causes. Due to the lack of effective pharmaceutical treatments for dementia, there are growing clinical and research interests in using vagus nerve stimulation (VNS) as a potential non-pharmacological therapy for dementia. However, the extent of the research volume and nature into the effects of VNS on dementia is not well understood. This study aimed to examine the extent and nature of research activities in relation to the use of VNS in dementia and disseminate research findings for the potential utility in dementia care.